Pengaruh Sikap dan Pengetahuan Kewirausahaan Terhadap Kesiapan Berwirausaha Dengan Self-Efficacy Sebagai Variabel Intervening - Andika Isma; Muhammad Rakib; Nurul Mufida; Mahmudatus Sholihah (CV. Sakura Digital Nusantara, 2023)
This study aims to test the entrepreneurial readiness model by presenting self-efficacy as an intervening variable that mediates the relationship between entrepreneurial attitudes and entrepreneurial knowledge. The population in this study was all students of the Entrepreneurship Study Program of Makassar State University which amounted to 300 students with a sample of 43 students. The research method used is the Quantitative method. The propotional random sampling technique was used to select a sample of 43 respondents from the Entrepreneurship Students of Makassar State University. Data collection with questionnaires, data analysis through Path Analysis. Based on the results of research that has been carried out, this can be a source of information or reference for teaching staff or lecturers in order to direct and guide students regarding the development of Entrepreneurship readiness, students are expected to further deepen attitudes and knowledge related to business management. but also able to do business ventures and develop them.